An evaluation of the midwifery Pre-Qualifying Skills Passport in Wales - Susanne Darra (British Journal of Midwifery, 2019)
This paper reports on a survey of users of a Pre-Qualifying Skills Passport for Student Midwives in Wales. It provides evidence from 167 users of the Passport. The respondents included students, mentors, teachers, managers and newly qualified midwives. The Passport was generally found to be of help in relation to knowledge and skill acquisition. The findings may inform current and future development of Midwifery Education Standards.